KOORDINASI PEMERINTAHAN DALAM PROGRAM RESTORASI GAMBUT DI DESA SUNGAI TOHOR KABUPATEN KEPULAUAN MERANTI TAHUN 2020-2021 - Fabiyanto, Erlan; Handoko, Tito (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The Peat Restoration Agency has the main task of coordinating and facilitating the acceleration of the implementation of peat restoration as well as efforts to improve community welfare in work areas in each province that has been determined, one of which is Riau Province. There are 3 programs that are the focus of restoration, namely Rewetting (wetting), Revegetation (greening) , and Revitalization (revitalization of the community's economy). In implementing the BRG program, TRGD is assisted in the regions to coordinate down to the village. This research aims to determine the coordination carried out by the Government and determine the factors that influence government coordination in the Peat Restoration program in Sungai Tohor Village, Meranti Islands Regency in 2020-2021. This research method is descriptive qualitative. Data collection uses interviews and documentation. This research was conducted in Sungai Tohor Village, Meranti Islands Regency. The research results show that government coordination in the peat restoration program is seen from vertical coordination, namely that the provincial TRGD directly coordinates with the Village without involving community groups and NGOs in the Village, then Horizontal coordination shows the results that the formation of work teams by the Village still prioritizes the team's closeness to the Village and there are still strongholds between community groups. Furthermore, there are two factors that influence government coordination in the implementation of the Economic Revitalization Program which are caused by the lack of unity of action and the lack of discipline among community group members in managing the assistance that has been provided. Keywords: Coordination, Governance, Peat Restoration Program